Income maintenance payments in Ireland, 1953-1971 - cyclical variations and long-term growth - Walsh, BM (Economic & Social Studies, 1974)
Three contributions have appeared in recent issues of this Review on the topic of Ireland's social security payments viewed in relation to the growth of national income. The original Note by Geary clearly raised some very important issues. In their Comment, O'Hagan and O'Higgins questioned the validity of Geary's approach, while not directly disagreeing with his main conclusion. The Rejoinder by Geary left some o f their objections unanswered. In the present brief study, I should like to return to the methodology of Geary's Note, in the hope of extending the analysis and shedding some further light on the factors affecting the growth of social security payments in Ireland.
Keywords: Social payments; Ireland